The Influence Of Organizational Culture And Work Environment On Employee Performance With Work Motivation As A Variable Intervening - Ismartaya, Ismartaya; Kartini, Tini; Safuan, Safuan; Halizah, Insani Nur; Apriyadi, Darmawan (Politeknik APP Jakarta, 2024)
To ascertain the overall, direct, and indirect effects of organisational culture and work environment on employee performance as measured by work motivation Discover the impact of work motivation intervening variables that mediate between organisational culture and work environment and employee performance at PT Lintang Gemini Abadi. Discover the impact of work motivation intervening variables that mediate between organisational culture and work environment and employee performance at PT Lintang Gemini Abadi.This study aims to ascertain the effect of work motivation intervening variables that mediate between organisational culture and work environment on employee performance at PT Lintang Gemini Abadi. It also aims to ascertain the direct, indirect, and overall influence of organisational culture and work environment on employee performance through work motivation. In this study, 100 respondents made up the sample—a proposed random sampling. The programme Microsoft Office Excel was used to transform ordinal data into metric data on an interval scale using the Method of Successive Interval (MSI). analysis of data employing path analysis (Path Analysys), verification analysis, descriptive analysis, and analysisUsing the IBM SPPS Version 25.00 programme, do the Sobel Test for variables that may be interfering. The study's findings demonstrate that organisational culture and work environment have a positive and significant impact on job motivation at the same time. Work motivation is positively and significantly impacted by organisational culture. Work motivation is positively and significantly impacted by the workplace environment. Employee performance is positively and significantly impacted by organisational culture. Employee performance is positively and significantly impacted by the workplace. Employee performance is positively and significantly impacted by work motivation. The workplace environment has the power to moderate employee performance through job motivation, whereas organisational culture is unable to do so.